Pelatihan Pemanfaatan Virtual Laboratory Berbasis PhET Simulation dalam Pembelajaran IPA bagi Guru di SMPN 27 Makassar - Musawwir Usman; Banu Kisworo; Zulqifli Alqadri; Syarful Annam; Yulianti Yusal (Postgraduate Program, University of Mataram, 2026)
Limited laboratory facilities and the low utilization of technology in science learning are among the main challenges in improving students’ conceptual understanding, particularly for abstract topics. One possible solution is the use of a virtual laboratory based on PhET Interactive Simulations. This Community Service Program (PKM) aims to enhance teachers’ understanding and skills in utilizing virtual laboratory-based learning media. The activity was conducted in the form of training for teachers at UPT SPF SMPN 27 Makassar using the Participatory Rural Appraisal (PRA) method. The implementation consisted of three stages: preparation, implementation, and evaluation. Data were collected through observation, questionnaires, and participant feedback. The results indicate that the training was successfully carried out and received positive responses from participants, with satisfaction levels categorized as very good (above 80%). Furthermore, teachers demonstrated improved understanding and skills in using PhET Simulation as a learning medium, particularly in explaining abstract science concepts. Therefore, this training can serve as an alternative solution to overcome laboratory limitations and support more interactive, visual, and meaningful learning.